Analisis Dasar Gugatan Konsumen atas Kerugian akibat Tindakan Filler oleh Klinik Kecantikan berdasarkan Kitab Undang-Undang Hukum Perdata - Raissa Maxentia (CV Rewang Rencang, 2025)
Beauty clinics are growing very rapidly in Indonesia but have many negative sides, sometimes patients experience side effects in their use and actually worsen the patient's beauty condition. This research delves into the nature of the doctor-patient interaction and the factors that give rise to consumer lawsuits over filler procedures that end up costing people money. From a Normative Juridical perspective, the research demonstrates that filler operations are founded on inspanning verbintenis, a legal connection between patients and doctors that establishes rights and responsibilities for both parties. The patient can seek material and immaterial damages as compensation in an action for Unlawful Acts based on Article 1365 of the Civil Code if they suffer losses as a result of a doctor's filler operations.